Konsep Matching dalam Tradisi Kumpul Keluarga Masyarakat di Nusa Tenggara Timur - Tallo, Richardus Engel; Pati, Stefanus Aldisusanto; Tito, Marianus; Hambur, Oktavianus; Lian, Yohanes Pemandi (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
Family gathering activities in East Nusa Tenggara (NTT) are a social tradition involving the collection of funds, goods, or animals during significant events such as marriages or funerals. This practice serves as a form of solidarity and mutual assistance within the community. Although these gatherings can incur substantial costs, the financial implications differ from ordinary accounting concepts. This research aims to explore the concept of